(3efGbH GdEeGe GdTGaYjs - (3GdHjgbj , CHh HcQ CMeO Hf GdMSjf Hf Ydj GdHjgbj GdNQGSGfj GdTGaYj, GdHjgbj,J (B458 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdChd GdQH GdQMje s
(3HChdgG Jedc ddYdGeI jMji Hf MLj GdTGaYj eDQN SfI (B850 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B116 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B206s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B363 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B156 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(2818) s
Keywords: (3GdJGQjNs